Eyewitness descriptions without memory: The (f)utility of describing faces. Issue 3 (29th February 2020) - Kramer, Robin S. S.; Gous, Georgina
Summary: Eyewitness descriptions provide critical information for the police and other agencies to use during investigations. While researchers have typically considered the impact of memory, little consideration has been given to the utility of facial descriptions themselves, without the additional memory demands. In Experiment 1, participants described face images to their partners, who were then required to select these faces from photographic lineups. Performance was error‐prone when the same image appeared in the lineup (73% correct), and decreased further when a different image of the same face was presented (22% correct). We found some evidence to suggest this was due, in part, to difficulties with recognizing that two different images depicted the same person. In Experiment 2, we demonstrated that descriptions of the same face given by different people showed only moderate agreement. Taken together, these results highlight the problematic nature of facial descriptions, even without memory, and their limited utility.